Patient experiences and perceptions of chronic disease care during the COVID-19 pandemic in India: a qualitative study. Issue 6 (18th June 2021) - Singh, Kavita; Kaushik, Aprajita; Johnson, Leslie; Jaganathan, Suganthi; Jarhyan, Prashant; Deepa, Mohan; Kong, Sandra; Venkateshmurthy, Nikhil Srinivasapura; Kondal, Dimple; Mohan, Sailesh; Anjana, Ranjit Mohan; Ali, Mohammed K; et al.
Abstract : Objective: People with chronic conditions are known to be vulnerable to the COVID-19 pandemic. This study aims to describe patients' lived experiences, challenges faced by people with chronic conditions, their coping strategies, and the social and economic impacts of the COVID-19 pandemic. Design, setting and participants: We conducted a qualitative study using a syndemic framework to understand the patients' experiences of chronic disease care, challenges faced during the lockdown, their coping strategies and mitigators during the COVID-19 pandemic in the context of socioecological and biological factors. A diverse sample of 41 participants with chronic conditions (hypertension, diabetes, stroke and cardiovascular diseases) from four sites (Delhi, Haryana, Vizag and Chennai) in India participated in semistructured interviews. All interviews were audio recorded, transcribed, translated, anonymised and coded using MAXQDA software. We used the framework method to qualitatively analyse the COVID-19 pandemic impacts on health, social and economic well-being. Results: Participant experiences during the COVID-19 pandemic were categorised into four themes: challenges faced during the lockdown, experiences of the participants diagnosed with COVID-19, preventive measures taken and lessons learnt during the COVID-19 pandemic. A subgroup of participants faced difficulties in accessing healthcare while a few reported using teleconsultations. Most participants reported adverse economic impact of the pandemic which led to higher reporting of anxiety and stress. Participants who tested COVID-19 positive reported experiencing discrimination and stigma from neighbours. All participants reported taking essential preventive measures. Conclusion: People with chronic conditions experienced a confluence (reciprocal effect) of COVID-19 pandemic and chronic diseases in the context of difficulty in accessing healthcare, sedentary lifestyle and increased stress and anxiety. Patients' lived experiences during the pandemic provide important insights to inform effective transition to a mixed realm of online consultations and 'distanced' physical clinic visits.